Earthworm effects on the incorporation of litter C and N into soil organic matter in a sugar maple forest. Issue 5 (1st July 2013) - Fahey, Timothy J.; Yavitt, Joseph B.; Sherman, Ruth E.; Maerz, John C.; Groffman, Peter M.; Fisk, Melany C.; Bohlen, Patrick J.
Abstract : To examine the mechanisms of earthworm effects on forest soil C and N, we double‐labeled leaf litter with 13 C and 15 N, applied it to sugar maple forest plots with and without earthworms, and traced isotopes into soil pools. The experimental design included forest plots with different earthworm community composition (dominated by Lumbricus terrestris or L. rubellus ). Soil carbon pools were 37% lower in earthworm‐invaded plots largely because of the elimination of the forest floor horizons, and mineral soil C:N was lower in earthworm plots despite the mixing of high C:N organic matter into soil by earthworms. Litter disappearance over the first winter–spring was highest in the L. terrestris (T) plots, but during the warm season, rapid loss of litter was observed in both L. rubellus (R) and T plots. After two years, 22.0% ± 5.4% of 13 C released from litter was recovered in soil with no significant differences among plots. Total recovery of added 13 C (decaying litter plus soil) was much higher in no‐worm (NW) plots (61–68%) than in R and T plots (20–29%) as much of the litter remained in the former whereas it had disappeared in the latter. Much higher percentage recovery of 15 N than 13 C was observed, with significantly lower values for T than R and NW plots. Higher overwinter earthworm activity in T plots contributed to lower soil N recovery. In earthworm‐invaded plots isotope enrichment was highest in macroaggregates and microaggregates whereas in NW plots silt plus clay fractions were most enriched. The net effect of litter mixing and priming of recalcitrant soil organic matter (SOM), stabilization of SOM in soil aggregates, and alteration of the soil microbial community by earthworm activity results in loss of SOM and lowering of the C:N ratio. We suggest that earthworm stoichiometry plays a fundamental role in regulating C and N dynamics of forest SOM.